Determination of obesity, physical activity and body fat percentage among women textile traders in central market Siti Khadijah and Bazaar Buluh Kubu, Kota Bharu, Kelantan - Yi, Cindy Lee Xiang (Universiti Sains Malaysia, 2015)
Assessment of nutritional status and body fat percentage was carried out on 182 women textile traders in Central Market Siti Khadijah and Bazaar Buluh Kubu, Kota Bharu, Kelantan. Data was collected using a questionnaire which included socio-demographic characteristics, the International Physical Activity Questionnaire (IPAQ), 24 hour dietary recall and Food Frequency Questionnaire (FFQ). Body mass index (BMI), waist circumference and waist-hip ratio were measured using standardized methods. The mean age of the respondents was 33.5 ± 12.5 years. The majority of the respondents were Malay (98.4 %) with 1.1% being Chinese and 0.5% other races. The mean weight, height and BMI were 57.8 ± 13.1 kg. 1.55 ±0m. 24.2 ± 5.2 kg/m" respectively. Based on WHO classification. 25.3% and 13.7% were overweight and obese respectively. Using waist circumference, waist-to-hip ratio and body fat percentage, prevalence of obesity were 42.9%. 52.2% and 42.3% respectively. A total of 19.2% of respondents had low' physical activity level, while 71.4% and 9.3% were in the moderate and high physical activity categories. Out of the respondents, 89.6% of them consumed cooked rice at least once daily (one plate per day), other food items consumed daily were marine fish (one medium fish per day), green leafy vegetables (% cup per day), and chicken (one medium per day). The mean calorie intake of respondents was 1063 ± 324.4 kcal, with 18.0% from protein. 26.0% from fat and 56.0% from carbohydrate. Significant linear relationship was found between age (b = 0.12. 95% CI = 0.06. 0.18, p 0.001). number of children (b = 0.35. 95% Cl = 0.00, 0.69. p 0.05) and protein intake (b = -0.038. 95% Cl = -0.076. 0.000. p 0.05) with BMI. Age, number of children and protein intake were predictors to obesity. However, no association was identified between physical activity with obesity.